2020
DOI: 10.3390/ijerph18010047
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Jetlag on Sleep Quality among Nurses: A Cross-Sectional Survey

Abstract: Social jetlag (SJL) refers to an asynchrony between one’s chronotype and social working hours, which can be detrimental to health. The current SJL situation in shift nurses who work in dysregulation is poorly understood. Therefore, this study aimed to investigate SJL during night shifts and identify the predictors of sleep quality in rotating shift nurses. A cross-sectional study was conducted in 2018 on a sample of 132 shift-working nurses from two general hospitals in South Korea (the response rate was 88.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Our small cohort demonstrated slightly higher levels of SJL on average (~2 h), with only two cadets having <1 h SJL. This is actually similar to the average SJL reported for a population of night shift nurses [ 37 ], indicating rather extreme desynchrony between ROTC-related schedules and social clocks. Though several studies have found a relationship between SJL and chronotype (indicating evening types have a greater discrepancy between work and social clocks) [ 24 , 38 ], we observed weak associations between SJL and MEQ scores (R 2 = 0.09), as well as SJL and SD (R 2 < 0.01, data not shown).…”
Section: Discussionsupporting
confidence: 85%
“…Our small cohort demonstrated slightly higher levels of SJL on average (~2 h), with only two cadets having <1 h SJL. This is actually similar to the average SJL reported for a population of night shift nurses [ 37 ], indicating rather extreme desynchrony between ROTC-related schedules and social clocks. Though several studies have found a relationship between SJL and chronotype (indicating evening types have a greater discrepancy between work and social clocks) [ 24 , 38 ], we observed weak associations between SJL and MEQ scores (R 2 = 0.09), as well as SJL and SD (R 2 < 0.01, data not shown).…”
Section: Discussionsupporting
confidence: 85%
“…However, social jet lag does not exclusively affect adolescents, as it has also been reported in shift workers, whose work during the night leads to a desynchronization of the circadian rhythm [191], and in young adults [192]. In contrast, not all populations showed a great social jet lag manifestation; for example, the Chinese population reported the social jet lag less frequently than the European population, and it was not correlated with higher BMI as it typically is in western societies [193].…”
Section: Chronotype and Social Jet Lagmentioning
confidence: 86%
“…As they are working in a three‐shift schedule, the daily routine often changes according to the shift work. Shift workers are more severely affected by social jetlag than nonshift workers because of the continuously changing work schedule, in addition to temporary disturbances in their circadian rhythm (Hulsegge et al, 2019; Kang et al, 2021). This is consistent with previous studies that reported that social jetlag affects depression (Islam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%